2006
DOI: 10.1002/tea.20123
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual boundaries and distances: Students' and experts' concepts of the scale of scientific phenomena

Abstract: To reduce curricular fragmentation in science education, reform recommendations include using common, unifying themes such as scaling to enhance curricular coherence. This study involved 215 participants from five groups (grades 5, 7, 9, and 12, and doctoral students), who completed written assessments and card sort tasks related to their conceptions of size and scale, and then completed individual interviews. Results triangulated from the data sources revealed the boundaries between and characteristics of sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
160
2
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(177 citation statements)
references
References 16 publications
7
160
2
8
Order By: Relevance
“…In the other domains, research on mental models in learning has provided theories to explain processes and difficulties related to acquiring concepts and building accurate representations of situations depicted in texts and other external representations. This approach has been found as particularly adapted for scientific learning (e.g., Tretter et al, 2006a).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other domains, research on mental models in learning has provided theories to explain processes and difficulties related to acquiring concepts and building accurate representations of situations depicted in texts and other external representations. This approach has been found as particularly adapted for scientific learning (e.g., Tretter et al, 2006a).…”
Section: Related Workmentioning
confidence: 99%
“…An interactive vr tool may contribute to promoting awareness and learning of the different aspects of nanoscale phenomena by providing a dynamic and more accurate direct experience of these phenomena (Tretter et al, 2006a;Park et al, 2010) through both visual and haptic feedback. Moreover, as the use of analogies has been shown as helpful for learning in physics (Podolefsky and Finkelstein, 2006), we were interested in evaluating the benefit of using macro-scale notions for the understanding of more exotic nanoscale phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Students from elementary through PhD, including those with visual impairments, estimate linear spatial magnitude better at human scales and worse at the extremes of scale, nanoscale to astronomical (Tretter et al, 2006a(Tretter et al, , 2006bJones et al, 2008Jones et al, , 2009aJones et al, , 2009b. Typically, the magnitudes of small-scale objects are overestimated, while the sizes of large-scale ones are underestimated; however, one study found that college students both under-and overestimate the sizes of small objects (Gerlach et al, 2014a).…”
Section: Conceptions Of Scale As Magnitudementioning
confidence: 99%
“…In contrast, estimation accuracy for objects at the microscopic level or smaller is discontinuous. There is a propensity to judge objects at scalar extremes as more similar in size than they actually are (Tretter et al, 2006a(Tretter et al, , 2006bJones et al, 2009bJones et al, , 2008. Those error patterns persist even when students use a model to support their explanations, specifically a scale model to illustrate astronomical distances.…”
Section: Conceptions Of Scale As Magnitudementioning
confidence: 99%
See 1 more Smart Citation